2013
DOI: 10.1039/c2cc36755f
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mass spectrometry on the study of intact antibodies: from post-translational modifications to structural analysis

Abstract: Monoclonal antibodies (mAbs) are important therapeutics, targeting a variety of diseases ranging from cancers to neurodegenerative disorders. In developmental stages and prior to clinical use, these molecules require thorough structural characterisation, but their large size and heterogeneity present challenges for most analytical techniques. Over the past 20 years, mass spectrometry (MS) has transformed from a tool for small molecule analysis to a technique that can be used to study large intact proteins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 111 publications
(156 reference statements)
0
49
0
Order By: Relevance
“…Native MS keeps the noncovalent interactions and fold of a protein largely intact and thus allows in-depth analysis of, e.g., stability, binding properties and conformation, which can also be useful to obtain information on glycosylation [43,75]. Furthermore, native MS shows a more concise chargestate distribution than conventional denaturing approaches, often resulting in higher signal-tonoise ratios and reduced spectrum complexity [43].…”
Section: The Future Of Drug Glycosylation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Native MS keeps the noncovalent interactions and fold of a protein largely intact and thus allows in-depth analysis of, e.g., stability, binding properties and conformation, which can also be useful to obtain information on glycosylation [43,75]. Furthermore, native MS shows a more concise chargestate distribution than conventional denaturing approaches, often resulting in higher signal-tonoise ratios and reduced spectrum complexity [43].…”
Section: The Future Of Drug Glycosylation Analysismentioning
confidence: 99%
“…LC-MS is commonly applied in reversed-phase (RP) or size-exclusion chromatography modes with ESI-TOF-MS detection [43,48]. Advantages in intact protein MS are high reproducibility and speed due to minimal, if any, sample preparation [42,43]; also, potential impurities may be detected within the same run. Notably, if multiple glycosylation sites are present, leading to a higher degree of heterogeneity, intact protein MS and MS/MS (top-down approach) will become challenging [42].…”
Section: Lc-esi-ms and Lc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive detection of phosphorylated proteins is required for understanding the disease mechanisms and the development of early diagnostic technologies. Mass spectrometry (MS) has become an indispensable tool for analysis of various biomolecules including phosphoproteins or phosphopeptides (Polat and Ozlu 2014;Leitner et al 2011;Chambers et al 2012;Jünger and Aebersold 2014;Gong et al 2014;Lin et al 2016; Thompson et al 2013). However, phosphorylated proteins are frequently masked by a large number of non-phosphorylated proteins or other biomolecules inside the cells.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 During recent years, several authors have successfully demonstrated the application of native MS for the qualitative and quantitative structural characterization of recombinant antibodies and new therapeutic protein formats. [29][30][31][32][33][34][35][36][37][38] Moreover, native MS also allows the analysis of dimer formation, antibody aggregation, and antibody-antigen binding. [39][40][41] For our study, an approach employing oxidative stress conditions and quantitative LC-MS peptide mapping combined with native MS for the simultaneous induction, quantification and functional assessment of Met oxidation in recombinant antibodies was developed.…”
Section: Introductionmentioning
confidence: 99%